On the differential equations and asymptotic solutions for arithmetic asian-rate call options - Labrador, Jinky J.; Escaner, JoseMaria L. (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2013)
Asian options are securities whose payoff depends on the average of the underlying stock prices over a certain period of time. A variety of techniques have been developed to analyze arithmetic asian options.Dewynne and Shaw (2007) presented a way of pricing asian rate call options using partial differential equation and obtained an asymptotic solution of the reduced underlying risk-neutral stochastic differential equation. In this study, we make some modifications on their partial differential equation and asymptotic solution and we provide more detailed computation on such methods.
Thesis (M.S.-Applied Mathematics) --University of the Philippines Diliman
Keywords: Differential equations -- Asymptotic theory